Associations Between Sign Language Skills and Resting-State Functional Connectivity in Deaf Early Signers - Holmer, Emil; Schönström, Krister; Andin, Josefine (Frontiers in Psychology, 2022)
The processing of a language involves a neural language network including temporal, parietal, and frontal cortical regions. This applies to spoken as well as signed languages. Previous research suggests that spoken language proficiency is associated with resting-state functional connectivity (rsFC) between language regions and other regions of the brain. Given the similarities in neural activation for spoken and signed languages, rsFC-behavior associations should also exist for sign language tasks. In this study, we explored the associations between rsFC and two types of linguistic skills in sign language: phonological processing skill and accuracy in elicited sentence production. Fifteen adult, deaf early signers were enrolled in a resting state functional magnetic resonance imaging (fMRI) study. In addition to fMRI data, behavioral tests of sign language phonological processing and sentence reproduction were administered. Using seed-to-voxel connectivity analysis, we investigated associations between behavioral proficiency and rsFC from language-relevant nodes: bilateral inferior frontal and posterior superior temporal gyri. Results showed that worse sentence processing skill was associated with stronger positive rsFC between left inferior frontal gyrus and left sensorimotor regions. Further, sign language phonological processing skill was associated with positive rsFC from right inferior frontal gyrus to middle frontal gyrus/frontal pole, although this association could possibly be explained by domain-general cognitive functions. Our findings suggest a possible connection between rsFC and developmental language outcomes in deaf individuals.